PENUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus Ostreatus ) PADA MEDIA SORGUM DAN ANALISIS FOURIER TRANSFORM INFRARED ( FTIR ) - Lusia Anita Br. Sagala; Erni Aprilina; Abu Sonip; Maya Risanti; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The successful establishment of oyster mushroom seeds depend on Potato Dextrose Agar (PDA). In this study,the sterilization level of media varied from level 1 to 3. For each sterilization level, PDA were steamed at 102 0C for 60 minutes. The best result was found at third level that was showed by growing of mycelium. All of spread seeds (F1) produced were good and not contaminated. The result of growing spread seeds by using sorghum media were not contaminated. The characterization result of FTIR mycelium from pure culture (F0), spread seeds (F1), and planting seeds (F2) indicated the stretching vibration. Stretching vibration showed of several functional groups. They were C-O, C-N, C=O, C-H, O-H, and Î²-D-glukan. Keywords: FTIR, functional groups, mycelium, sorghum media.